Propuesta de un manual de seguridad y salud ocupacional para el talento humano de la empresa PROCEPALMA S.A. de la ciudad de Santo Domingo de los Tsachilas - Cifuentes Márquez, Mónica Alexandra (2016)
This research project is within the Company Procepalma SA, extraction plant Santo DOMINGO, for "PROPOSAL FOR A MANUAL FOR OCCUPATIONAL SAFETY AND HEALTH HUMAN TALENT ENTERPRISE PROCEPALMA SA CITY OF SANTO DOMINGO" which emerged as a result of research based on techniques that have provided key staffing needs of the enterprise information Procepalma SA It is a company belonging to the vegetable oil sector; for the extraction of palm kernel oil. In order to safeguard the welfare of their employees and ensure their satisfaction within the company, the need to implement a Security Manual occupational health and complying with the provisions of the law is generated. He polled 24 workers, and one interview to the General Manager. The study presented below, seeks to determine the conditions under which the company is located, its structure, equipment, machines and tools, as well as the health of all employees; and the analysis of the processes taking place there and the evaluation of each job, identify risks that can cause accidents and incidents of work; all this in order to propose possible solutions to reduce or eliminate those risks, which will be achieved through design Manual Occupational Safety and Health, in which the comprehensive assessment of working conditions and health requirements, policies program, and the activities undertaken in the subprograms of preventive and occupational medicine and hygiene and safety.